2020
DOI: 10.1039/d0lc00106f
|View full text |Cite
|
Sign up to set email alerts
|

A disposable acoustofluidic chip for nano/microparticle separation using unidirectional acoustic transducers

Abstract: A disposable acoustofluidic platform was developed for nano/microparticle separation with high versatility, precision, and biocompatibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 69 publications
1
63
0
Order By: Relevance
“…Despite valuable provided insight of 2D simulations in acoustofluidic problems, the developed 3D model can overcome their limitations in capturing the impression of established SSAW and taSSAW field non-uniformities along the channel length on the particle trajectory, and final inter-particle distance at channel outlet under highly interactive involved parameters. The presented 3D model would have sufficient capability and versatility to be adopted to simulate novel complex on-chip configuration like taSSAW microfluidic devices 21 and disposable acoustofluidic chips 44 . Furthermore, it helps to make a more accurate prior approximation for 2D simplification of the favorable device, which might not always be straightforward.…”
Section: Resultsmentioning
confidence: 99%
“…Despite valuable provided insight of 2D simulations in acoustofluidic problems, the developed 3D model can overcome their limitations in capturing the impression of established SSAW and taSSAW field non-uniformities along the channel length on the particle trajectory, and final inter-particle distance at channel outlet under highly interactive involved parameters. The presented 3D model would have sufficient capability and versatility to be adopted to simulate novel complex on-chip configuration like taSSAW microfluidic devices 21 and disposable acoustofluidic chips 44 . Furthermore, it helps to make a more accurate prior approximation for 2D simplification of the favorable device, which might not always be straightforward.…”
Section: Resultsmentioning
confidence: 99%
“…Comparing with the SSAW, the TaSSAW has the ability to separate the particles with a larger distance, enabling highly efficient and sensitive separation. Using TaSSAWs, Zhao et al demonstrated a disposable device that can separate particles with a wide range from 200 nm to 10 µm [ 80 ]. Instead of changing the geometry of the IDT, Rambach et al introduced a simple and flexible separation technique for different-sized particles which enables shaping of the SSAW by shifting the PDMS foil’s geometry [ 81 ].…”
Section: Saw-based Separationmentioning
confidence: 99%
“…As previously discussed in the cell sorting section, SAW is a technique often utilized in BioMEMS devices. Zhao et al described a disposable PDMS acoustofluidic chip for nano/microparticle separation [28]. The authors demonstrated the use of a hybrid channel design with hard and soft materials and tilted-angle standing SAWs.…”
Section: Laser Cutting Plasma-activated Bondingmentioning
confidence: 99%